Where to find structural grade timber: a case study in ponderosa pine based on stand and tree level factors - Caballe, Gonzalo; Santaclara, Oscar; Diez, Juan Pablo; Letourneau, Federico Jorge; Merlo, Esther; Martinez Meier, Alejandro (Elsevier, 2020)
Using portable acoustic tools, measurements of dynamic modulus of elasticity (Ed) were made in standing ponderosa pine (Pinus ponderosa (Dougl. ex Laws)) trees (n =437) growing in 22 stands encompassing the range of environmental site conditions and ages of the plantations that have been established in NW Patagonia, Argentina. The objectives of this research were to (i) identify the stand and tree-level factors associated with the variation in Ed and, with the most suitable variables (ii) develop a descriptive model to Ed for ponderosa pine grown in NW Patagonia Argentina as the first step of a predictive model. Tree and stand variables showed a wide range of variation and Ed ranged ten-fold, from 2.13 GPa to 22.1 GPa, with a mean value of 11.2 Gpa. The cross-correlations analysis performed among Ed and independent tree and stand variables showed almost all variables to be significantly related to Ed. The main positive and significant correlation was found for total tree height (H, r = 0.78, p < 0.001), top height of the stand (H100, r = 0.78, p < 0.001) and basal area of the stand (G, r = 0.68, p < 0.001). Nevertheless, the most suitable independent variables for modelling Ed were two stand variables: age at breast height (ABH) and site index (SI20) and two tree variables: stem slenderness (S, tree height/diameter at breast height) and social status or relative height (RH = H/H100). In combination, ABH, SI20, S and RH accounted for 68.4% of the variation in Ed within the sample population. This model could be readily applied by managers to estimate stand-level Ed, giving them greater understanding of how they can manipulate stands to achieve desired end product outcomes.